High ligand density drives extensive spreading and motility on soft GelMA gels. (13th August 2021) - George, Edna; Jahan, Iffat; Barai, Amlan; Ganesan, Vignesh; Sen, Shamik
Abstract: In comparison to synthetic hydrogels where ligand density and stiffness can be independently tuned, cell responses are expected to deviate on native biopolymer networks where ligand density and stiffness are coupled. Here we probe the tensional homeostasis of fibroblasts on methacrylated gelatin (GelMA) gels, which are widely used in tissue engineering applications. On 5%–15% GelMA gels which are very soft (10–100's of Pa's in stiffness), fibroblasts were found to spread extensively and assemble prominent stress fibers and focal adhesions. Probing of contractile mechanics using trypsin-induced detachment revealed adhesive drag, but not contractility, was sensitive to GelMA concentration. Contractility-altering drugs blebbistatin and nocodazole, which exhibited opposite effects on focal adhesion size, both led to reduction in adhesive drag and cell rounding. However, cell motility was impacted only in nocodazole-treated cells. Collectively, our experiments suggest that on soft GelMA gels, contractility-independent adhesion clustering mediated by high ligand density can drive cell spreading and motility.